How far are we from full implementation of health promoting workplace concepts? A review of implementation tools and frameworks in workplace interventions. (8th January 2017) - Motalebi G., Masoud; Keshavarz Mohammadi, Nastaran; Kuhn, Karl; Ramezankhani, Ali; Azari, Mansour R
Abstract: Introduction: Health promoting workplace frameworks provide a holistic view on determinants of workplace health and the link between individuals, work and environment, however, the operationalization of these frameworks has not been very clear. This study provides a typology of the different understandings, frameworks/tools used in the workplace health promotion practice or research worldwide. It discusses the degree of their conformity with Ottawa Charter's spirit and the key actions expected to be implemented in health promoting settings such as workplaces. Method: A comprehensive online search was conducted utilizing relevant key words. The search also included official websites of related international, regional, and national organizations. After exclusion, 27 texts were analysed utilizing conventional content analyses. Results: The results of the analysis were categorized as dimensions (level or main structure) of a healthy or health promoting workplaces and subcategorized characteristics/criteria of healthy/health promoting workplace. Discussion and conclusion: Our analysis shows diversity and ambiguity in the workplace health literature regarding domains and characteristics of a healthy/health promoting workplace. This may have roots in lack of a common understanding of the concepts or different social and work environment context. Development of global or national health promoting workplace standards in a participatory process might be considered as a potential solution.